Design and Evaluation of an Automatic Roof Drive Prototype in Optimizing Tomato Cultivation - Budi Wibowo; Affan Nawly Tanjung; Nur Afandi; Tio Dwi Ananpasha; Taufik Hidayat (Sultan Publisher, 2025)
This study introduces the design and evaluation of an automatic roof drive prototype aimed at optimizing tomato cultivation. Developed to address the challenges of erratic weather, the system seeks to enhance the efficiency of tomato farming. The prototype integrates a weather sensor, microcontroller, and roof drive mechanism, allowing it to operate automatically based on real-time environmental conditions. Effectiveness was assessed through field trials measuring key growth parameters such as plant height, fruit number, and fruit quality. Results indicate that the automatic roof drive system significantly improves both the productivity and quality of tomato crops. Additionally, the system effectively mitigates losses due to extreme weather conditions, including heavy rain and excessive heat. These findings highlight the potential of automated roof drive technology to support more efficient and sustainable agriculture. Future work will focus on refining the system for broader applications and integrating advanced technologies such as IoT and machine learning for further optimization.